SELF LOVE EDUCATION ON TO MAINTAIN MENTAL HEALTH IN THE DIGITAL ERA TO CREATE A PRODUCTIVE, HEALTHY, AND HAPPY YOUNG GENERATION - Sety, La Ode Muhamad; Nurfadilah H, Siti; Handayani, Listy; Salsabila, Syefira; Rohadi, Melia Pradita; Arifin, Muhammad; Yasmin, Dhira Fijri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Mental health issues are the fifth largest contributor to the global disease burden and one of the main risk factors for morbidity and mortality among adolescents. This community service aims to increase teenagers' knowledge about the concept of self-love as an effort to maintain mental health. This activity was conducted at SMA Negeri 9 Kendari in November 2024 with the students as a target, totaling 30 people. The stages of this activity consisted of audience/socialization, data collection of prospective participants, identification of mental health issues among students, dissemination process (self-love education and distribution of flip charts, leaflets, and posters Medias to the school and Benu-Benua Health Center). As well as evaluation using the comparison of pre-test and post-test scores. All stages of this activity went well and smoothly, the school fully supported this activity, and the participants showed high enthusiasm during the education and discussion process. The evaluation result shows an increase in students' knowledge about self-love as an effort to maintain mental health after the education was conducted. Thus, it is hoped that schools and community health centers will regularly provide education on self-love to all students or adolescents to address potential mental health risks.